THE IMPACT OF THE DIGITAL ECONOMY ON INVESTMENT PORTFOLIO MANAGEMENT IN THE STOCK MARKET - Pereguda, Yuliya; Biloshkurskyi, Mykola (Public Management and Policy, 2026)
Digitalization in the stock market and the use of innovative data processing and analysis technologies have led to the emergence of new approaches to the formation of investment portfolios of different types of investors. The purpose of the article was to identify modern approaches to the formation of investment portfolios of different types of investors (retail, professional) in the context of the development of new technological sectors. It is proposed to consider an investment portfolio as a set of financial assets owned by an investor for a certain period of time and with a certain level of profitability depending on the level of risks taken. It is determined that the use of digital solutions in the formation of an investment portfolio contributes to a more rational approach to the selection of assets, reduces transaction costs for the acquisition of assets and increases the level of diversification of acquired financial assets. Under the influence of the digitalization of the economy and the emergence of new technological companies and startups, investors apply a dynamic approach to the formation of a highly diversified investment portfolio, combining in it the assets of exchange-traded investment funds, shares of companies from high-tech sectors and alternative assets (cryptocurrencies). A high level of prevalence of passive investment strategies through exchange-traded funds, an increase in the level of investment in shares of technology companies in new sectors of the economy, and a tendency to invest in high-risk and high-yield digital assets were revealed. It was found that digitalization and data analytics on digital platforms allow the development of personalized investment solutions using the recommendations of robo-advisors. The latter allows for a more balanced approach to investment based on rational, well-founded decisions made on the basis of data analytics. It was found that the use of algorithmic trading is a common phenomenon, which provides high liquidity in the stock market and minimizes risks for professional investors.